Association between caregiver burden and the presence of neurological alterations in a Peruvian geriatric population - Leiva-Socualaya, Steven Joseph (2023)
Objective: The objective of this study is to establish the association between caring for older adults with neurological disorders and suffering from caregiver burden at the Naval Geriatric Center of Peru, from November 2019 to January 2021. Methodology: Analytical, observational, cross-sectional study carried out at the Geriatric Center of the Naval Medical Center. A total of 290 older adult's caregivers who went to medical consultation were surveyed. Caregiver burden was measured with the Zarit burden scale. Results: A prevalence of caregiver burden of 52.76% was found. The patients that suffered some neurological alteration were 62.76%. When adjusting for sociodemographic variables, being the patient's spouse increased the probability of suffering from caregiver burden by 2.23 times. When adjusting for the variables related to care, caring for a patient with neurological disorder and caring for an older adult for 1 or 2 years increased the probability of suffering caregiver burden by 1.86 and 1.91 times, respectively, while having the support of other people decreased the probability of suffering it by 39%. Conclusions: Caregiver overload is associated with caring for an older adult with neurological disorder, being the patient's spouse, caring for 1 or 2 years and having the support of other people.